2022
DOI: 10.1109/jphot.2022.3207172
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-BICs Enabled Proximity Sensing Based on Metal Complementary H-Shaped Arrays at Terahertz Frequencies

Abstract: All metal sensing based on complementary H-shaped arrays (HSAs) is numerically and experimentally investigated at terahertz frequencies. The symmetry-protected bound states in the continuum (BICs) are activated by adjusting one arm's length of the H-shaped, enabling high-Q quasi-BICs. The Q-factor of quasi-BICs is modulated in terms of structural parameters and metal conductivity. With optimal structural parameters of copper HSAs, the proximity sensing performances are studied as a function of the film thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Incident waves with polarization that parallel to the metal grating are reflected, while the perpendicular polarization is transmitted. One of the biggest drivers for the research polarization control is the application of THz sensors [19][20][21][22][23][24]. For high-sensitivity sensing, the quality (Q) factor is crucial for metasurfaces-based sensors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Incident waves with polarization that parallel to the metal grating are reflected, while the perpendicular polarization is transmitted. One of the biggest drivers for the research polarization control is the application of THz sensors [19][20][21][22][23][24]. For high-sensitivity sensing, the quality (Q) factor is crucial for metasurfaces-based sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Such quasi-BICs possessing polarization-insensitive properties originate from guided mode resonances in metasurfaces via symmetry-breaking. Meal-dielectric or all-metal metasurfaces are also proposed for BICs manipulations although the Ohmic loss is not negligible [22,32,[42][43][44][45][46][47][48][49][50][51]. Kyaw et al reported an asymmetric split-ring resonator-based metasurfaces, realizing polarization-dependence of accidental BICs [32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By tuning the structural parameter, a maximum Q-factor of 102 of quasi-BICs can be measured. Subsequently, Wang et al used such kinds of BICs metasurfaces for polymer membrane sensing [ 24 ]. A sensitivity of 151 GHz/RIU for 50-μm polymer was obtained, higher than bulky dielectric substrate metamaterials.…”
Section: Introductionmentioning
confidence: 99%